ASPEK PENOLAKAN DALAM NOVEL â€œTHE GUARDIANâ€ KARYA NICHOLAS SPARKS (SUATU ANALISIS PRAGMATIK) - DJAPAI, MAGDALENA PRISCILIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Â Language is the most important part of human life. In communcation, people do not only utter sentence but also transfer it into behavior. Rejection is a form of communication. Rejectiom refusing something of the hearer and rejection belongs to perlocutionay act. Rejection can be divided into explisit rejection and implisit rejection. The collected data were identified and clasified in terms of explisit rejection and implisit rejection that found from the utterances of the characters. The identified and clasified data then analyzed descrptive based on the aspects of rejection (the aspects of perlocutionary act) that uttered by the characters of in the novel according to Leech (1983) and Crystal (1972) theory. The results show that there are two kinds of perlocutionary act found in the novel The Guardian by Nicholas Spark, those are explisit and implisit perlocutionary act whereas the aspects of rejection found in that novel are to get hearer to think, requesting, starting, and offering. Key WordsÂ Â Â Â Â :Â Rejection, Perlocutinary act, Pragmatics.